Patrol Activities in Preventing the Crime of Theft with Aggravated Circumstances During the Covid-19 Pandemic - Wahyu Fajar Dinata (Police Studies Review, 2021)
The Covid-19 pandemic is a condition in which a disease originating from the Covid-19 virus has spread throughout the world. This condition in the end has a very big impact on human life. This has resulted in many aspects of human life being disrupted, along with the onset of this pandemic, social problems have arisen. The social problems that arise are such as an increase in unemployment due to layoffs, a decline in the level of the economy such as production of goods, buying and selling transactions, and others. This has resulted in an increase in the level of crime that occurs in the community in the form of criminal cases such as theft. Therefore, necessary steps are needed to prevent crime in society, one of which is by carrying out police preventive activities. The form of the preventive function of the police is in the form of patrol activities to prevent the occurrence of criminal acts of theft with weight. This study aims to determine how Police Readiness efforts in patrol activities can prevent criminal acts of theft by using theories in the field of criminology and the concept of Sabhara and patrol in the jurisdiction of the Pekanbaru Police. Based on the results of the study, it was found that the increase in cases of theft was due to social problems arising from the Pandemic, the Ministry of Law and Human Rights assimilation program and the efforts made to prevent these cases from occurring through beat patrols and sambang patrols.